Auf den Spuren des Erb’schen Auskultationspunkts: Rätsel gelöst - Kolb, Frederick; Spanke, Johannes; Winkelmann, Andreas (DMW - Deutsche Medizinische Wochenschrift, 2018)
“Erb’s point” is the fifth point of auscultation for the heart exam, located in the third intercostal space close to the sternum. It has sometimes been attributed to famous German neurologist Wilhelm Heinrich Erb (1840 – 1921), but without historical evidence. Erb’s focus on neurology suggested that the auscultation point may have been confused with other points in the neck named after Erb. As Erb was a specialist for neurological manifestations of syphilis, we speculated that the heart murmur of aortic incompetence produced by syphilitic aortitis, best heard at Erb’s point, linked Erb’s name to the auscultation point. However, we eventually found a publication by an American physician who visited Erb’s lectures in Heidelberg and reported that Erb explicitly introduced this “fifth point” in his case presentations in the late 1890 s. After all, Erb was chair of general medicine, with the first German chair of neurology only being established in 1919.
Keywords: Wilhelm Heinrich Erb; Erb’scher Punkt; Herzauskultation; Aortenklappeninsuffizienz; Eponym